Localised 1H-MR spectroscopy for metabolic characterisation of diffuse and focal brain lesions in patients infected with HIV. Issue 4 (1st April 1998) - Simone, I L; Federico, F; Tortorella, C; Andreula, C F; Zimatore, G B; Giannini, P; Angarano, G; Lucivero, V; Picciola, P; Carrara, D; Bellacosa, A; Livrea, P
Abstract : OBJECTIVES: To evaluate the role of proton MR spectroscopy ( 1 H-MRS) in detecting metabolic changes in diffuse or focal lesions in the brain of patients infected with HIV. METHODS: Sixty HIV seropositive patients (25 with HIV related encephalopathies, 20 with toxoplasmosis, eight with progressive multifocal leukoencephalopathies (PMLs), and seven with lymphomas) and 22 HIV seronegative neurological controls were examined with a combined MRI and 1 H-MRS technique using a Siemens 1.5 Tesla Magnetom. Spectra (Spin Echo sequence, TE 135 ms) were acquired by single voxel, localised on focal lesions in toxoplasmosis, PML, lymphomas, and HIV encephalopathies and on the centrum semiovale of neurological controls. Choline (Cho), creatine (Cr), N-acetyl aspartate (NAA), lactate, and lipids were evaluated in each spectrum and NAA/Cr, NAA/Cho, and Cho/Cr ratios were calculated. RESULTS: A significant decrease in NAA/Cr and NAA/Cho ratios were found in all HIV diagnostic groups in comparison with neurological controls (p<0.003), suggesting neuronal or axonal damage independent of brain lesion aetiology. However, the NAA/Cr ratio was significantly lower in PML and lymphomas than in HIV encephalopathies (p<0.02) and toxoplasmosis (p<0.05). HIV encephalopathies, lymphomas, and toxoplasmosis showed a significant increase in the Cho/Cr ratio in comparison with neurological controls (p<0.03) without between group differences. The presence of a lipid signal was more frequent in lymphomas (71%) than in other HIV groups (Fisher's test, p=0.00003). The presence of mobile lipid resonance together with a high Cho/Cr ratio in lymphomas may be related to an increased membrane synthesis and turnover in tumour cells. A lactate signal (marker of inflammatory reaction), was found in all but one patient with PML lesions (75%), but had a lower incidence in the other HIV diagnostic groups (Fisher's test, p=0.00024). CONCLUSION: 1 H-MRS shows a high sensitivity in detecting brain involvement in HIV related diseases, but a poor specificity in differential diagnosis of HIV brain lesions. Nevertheless, the homogeneous metabolic pattern that characterises PML suggests the usefulness of 1 H-MRS as an adjunct to MRI in differentiating CNS white matter lesions, such as HIV encephalopathies, from PML.